Innovation in Combination of Massage Gun and Nigella Sativa Oil (NSO) to Prevent the Risk Of Decubitus - Sahid, Nur (Jurnal Multidisiplin Indonesia, 2024)
Decubitus ulcers often occur in the elderly because the condition of the elderly is susceptible to disease and requires complete rest (bed rest) due to decreased body function, which causes limitations in body movement. Decubitus wounds are caused by several factors, namely immobilization, friction, and skin moisture. Pressure sores can be treated in several ways, namely by massaging and improving blood circulation, especially in the pressure area. Massage using direct massage requires extra energy so that a massage gun can reduce fatigue risk. This massage gun can be applied with Niggella Sativa Oil (NSO) to help increase skin hydration and elasticity. Objective: To determine the effectiveness of administering a combination of a massage gun and Nigella Sativa Oil (NSO) to prevent the risk of pressure ulcers in the elderly at the Sasana Tresna Wonogiri Nursing Home. Giving Nigella Sativa Oil (NSO) alone is not very effective, so innovation is needed in this tool by adding a massage gun, which helps increase blood circulation so that it can help older people with long bed rest to reduce the risk of developing pressure ulcers.